Self-Mimetic Curved Silvering: Dancing with Irigaray - Joshua Maloy Hall (Journal of French and Francophone Philosophy, 2014)
In lieu of an abstract, here is the opening paragraph of the essay: One of Luce Irigaray’s many important contributions to philosophy consists in invoking dance more frequently than any other canonical Western philosopher. Unfortunately, however, her treatment of dance has rarely been treated substantively in the secondary literature, especially in regard to her most influential commentators, including Judith Butler, Elizabeth Grosz, and Margaret Whitford. Accordingly, I will begin my first section by situating the theme of dance in Irigaray’s work in the context of that of the latter three philosophers. I will attempt to show, moving from Butler to Grosz to Whitford, an increasing tolerance for, and ultimately even celebration of, ambivalence in the form and content of Irigaray’s work. I will then conclude my first section by considering Elend Summers-Bremer’s “Reading Irigaray, Dancing” in tandem with Gerald Jonas’ Dancing: The Power, Pleasure and Art of Movement. My suggestion here will be that a certain Irigaray-informed approach to social dance could be seen as foreshadowing Irigaray’s later work on a new, more positive, kind of heterosexual relationship. Overall, then, this first section provides the justification for my thematic focus on dance.